МЕТОДЫ РАЗВИТИЯ СОЦИАЛЬНОГО ИНТЕЛЛЕКТА КУРСАНТОВ - БУДУЩИХ ОФИЦЕРОВ ПОЛИЦИИ - Харченко, Светлана Вячеславовна (SUPREMANCE OF LAW, 2017)
The abilities of social intelligence and their interrelation with the behavior and personality of cadets - the future policy officers are analyzed. It is proven that a high level of social intellect is to important part of personality of modern officer of police. The basic terms of developing flairs of social intellect of cadets mark. The psychological and pedagogical methods of developing the abilities of social intelligence in the process of special training of future police in the university are described. Particular attention is paid to such methods of developing the abilities of social intelligence as socio-psychological training and film-training.